2018
DOI: 10.1002/jcp.27758
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA‐548c‐5p downregulates inflammatory response in preeclampsia via targeting PTPRO

Abstract: Preeclampsia is a serious complication of pregnancy and leads to maternal hypertension and proteinuria. It remains a major health problem for mothers and babies across the world due to high maternal and fetal morbidity and mortality. Accumulated data have implicated the critical role of microRNA in preeclampsia. However, to date, the role of miR‐548c‐5p in preeclampsia remains vaguely understood. In this study, we first elucidate the role of miR‐548c‐5p and its underlying molecular mechanism in preeclampsia. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
(59 reference statements)
0
37
0
Order By: Relevance
“…MiR‐548c‐5p is lowly expressed in serum exosomes and placental mononuclear cells in PE patients compared to normal pregnancies. MiR‐548c‐5p down‐regulation is associated with increased secretion of inflammatory cytokines (IL‐12 and TNF‐α) and nuclear translocation of NF‐κB in macrophages, which in turn triggers the proliferation and activation of macrophages and stimulates inflammatory response . Exosomes from GDM pregnancies increase the release of pro‐inflammatory cytokines from ECs, including GM‐CSF, IL‐6 and IL‐8, among others, similar to exosomes isolated from cells cultured under high glucose condition .…”
Section: Evs In Complicated Pregnancymentioning
confidence: 90%
See 1 more Smart Citation
“…MiR‐548c‐5p is lowly expressed in serum exosomes and placental mononuclear cells in PE patients compared to normal pregnancies. MiR‐548c‐5p down‐regulation is associated with increased secretion of inflammatory cytokines (IL‐12 and TNF‐α) and nuclear translocation of NF‐κB in macrophages, which in turn triggers the proliferation and activation of macrophages and stimulates inflammatory response . Exosomes from GDM pregnancies increase the release of pro‐inflammatory cytokines from ECs, including GM‐CSF, IL‐6 and IL‐8, among others, similar to exosomes isolated from cells cultured under high glucose condition .…”
Section: Evs In Complicated Pregnancymentioning
confidence: 90%
“…In peripheral blood from patients with PE, exosomal miR‐136, miR‐494 and miR‐495 are 6.4‐, 3.9‐ and 2.1‐fold higher than that in normal pregnancies, respectively, according to a study enrolling 100 PE patients . In addition, miR‐141, miR‐155 and miR‐548c‐5p are detected with altered expression in PE and identified as the candidate miRNA markers. During the first trimester of pregnancy, miR‐517‐5p, miR‐520a‐5p and miR‐525‐5p are observed to be down‐regulated in plasma exosomes of PE patients with later occurrence.…”
Section: Evs As Biomarkers For Pregnancy‐related Diseasesmentioning
confidence: 99%
“…A number of studies have implicated that PTPRO participates in the regulation of macrophage-mediated inflammatory response, hepatic ischemia reperfusion injury, and tumor immunity [ 32 35 ]. In our previous study, PTPRO has been demonstrated to be significantly upregulated in preeclampsia patients, which is also found to be involved in regulating macrophage inflammation in preeclampsia [ 36 ]. The current study has firstly suggested that PTPRO is upregulated in placenta-derived macrophages from gestational diabetes mellitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Block I et al has shown evidence that expression of hsa‐miR‐548c‐5p could affect the abridged disease‐free survival of breast cancer patients (Block et al, ). It has been documented that miR‐548c‐5p influence inflammation and the prognosis of CRC patients (Peng, Gu, & Yan, ; Wang et al, ). Nevertheless, little is known about the role of miR‐548c‐5p in CRC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%